Pemanfaatan Pengolahan Data Rekam Medis Untuk Statistik Asuhan Kesehatan Di RSUD M. Natsir Solok - Nisa Azhari; Yuli Mardi; Ressa Oashttamadea (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2021)
Data in health services is stored in the form of patient health records, which is a collection of various data elements in health records that are used to compare, combine, and present patient conditions by doctors and for health services. From the results of data processing, the most grouping of diagnoses based on ICD-10 is Gastroenteritis and colitic of unspecified with code A09.9 as many as 33 patients. Then the grouping based on the ICD-10 chapter is mostly in Chapter I (Certain Infectious and Paracitic Disease) with a percentage of 22.71% or 129 patients. The most grouping based on procedure was Tonsillectomy with ICD-9CM code 28.2 as many as 14 patients. The most grouping based on the DTD code and its definition was DTD 270.9 (Abnormal Clinical And Laboratory Symptoms, Signs and Findings, YTK elsewhere) as many as 35 patients. The grouping based on Table Format RL4a was the most in the 45-64 year age group as many as 143 patients with 71 female patients and 72 male patients. Grouping by address, the most sub- districts in Solok District/City are Kubung District with 111 patients. There were 554 patients alive with disposition and 14 patients died. After processing the data, statistical processing is carried out with the following results: the results of the BOR obtained are 60.55%. BOR has reached efficiency figures because the efficiency level of BOR is 60-85%. Then the BTR result is 9 times. BTR is not efficient because the calculation of BTR is done once a year with an efficiency level of 40- 50 times. For the results of TI is 2.71 days. TI efficiency is 1-3 days.